The HIV epidemic in Jamaica: a need to strengthen the National HIV Program - J. Peter Figueroa; Jacqueline P. Duncan; Althea Bailey; Nicola Skyers (Pan American Health Organization, 2020)
Objectives. To assess the status of the HIV epidemic and programmatic implementation in Jamaica while identifying strategies for achieving effective HIV control. Methods. The assessment included a review of the core indicators of the UNAIDS Global Monitoring Framework, a desk review of program reports, and unstructured interviews of stakeholders. Results. HIV prevalence among adults in Jamaica was 1.5% in 2018 with an estimated 32 617 persons living with HIV (PLHIV) and 27 324 persons (83.8%) diagnosed with HIV; 12 711 (39.0% of all PLHIV or 46.5% aware of their status) were on anti-retroviral therapy (ART) in the public health sector and 61.8% PLHIV on ART were virally suppressed. HIV prevalence among men who have sex with men remains high (31.4% in 2011, 29.6% in 2017) but has declined among female sex workers (12% in 1990, 2% in 2017). HIV prevalence among public sexually transmitted infection clinic attendees, prison inmates and the homeless has increased in recent years. During 2018 approximately 200 000 persons (14% of the population 15-49 years) were tested with 1 165 newly diagnosed PLHIV, indicating that many of the estimated 1 600 newly infected persons in 2018 were unaware of their status. Conclusions. Critical policy initiatives are needed to reduce barriers to HIV services, ensure young persons have access to condoms and contraceptives, affirm the rights of the marginalized, reduce stigma and discrimination, and introduce pre-exposure prophylaxis. While HIV spread in Jamaica has slowed, the UNAIDS Fast Track goals are lagging. The HIV program must be strengthened to effectively control the epidemic.